Reassessing Justice in Murabahah Regulation in Indonesia through Sayyid Qutb’s Perspective - Jefik Zulfikar Hafizd; Tajul Arifin; Hasan Bisri; Dedah Jubaedah (International Journal of Islamic Khazanah, 2026)
This article examines whether murābaḥah regulation and practice in Indonesia embody Islamic justice as a substantive ethical principle or remain confined to procedural sharia compliance. Existing studies on murābaḥah largely emphasize contractual validity, regulatory structure, and institutional compliance, but pay limited attention to justice as an ethical standard for evaluating how Islamic consumer finance operates in practice. Using a normative-conceptual method, this study analyzes primary legal and regulatory materials, including OJK regulations, statutory instruments, DSN–MUI fatwas, and internal supervisory guidelines, complemented by an interview conducted in November 2025 with an Assistant Manager at the OJK Regional Office in Cirebon. The analysis employs Sayyid Qutb’s framework of Islamic justice—mīzān, ḥurriyyah, and takāful ijtimāʿī—to assess the legal construction, regulatory objectives, and operational logic of murābaḥah within Indonesia’s Islamic financial system. The study finds that although murābaḥah has been regulated in a systematic and comprehensive manner to ensure legal certainty, prudential governance, and formal sharia compliance, such regulatory coherence does not automatically realize substantive Islamic justice. Market-oriented margin structures, debt-like operational features, and limited social orientation reveal a normative gap between procedural conformity and ethical justice. This article contributes to Islamic governance scholarship by offering a justice-centered evaluative framework for murābaḥah and by providing normative insights for strengthening Islamic consumer finance regulation beyond technical compliance toward a model that better integrates legal certainty, social justice, balanced risk allocation, and collective welfare.